Risks of ACE Inhibitor and ARB Usage in COVID-19: Evaluating the Evidence - Sriram, Krishna; Insel, Paul A (Clinical pharmacology and therapeutics, 2020)
Concerns have been raised regarding the safety of angiotensin converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) in patients with coronavirus disease of 2019 (COVID-19), based on the hypothesis that such medications may raise expression of ACE2, the receptor for severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2). We conducted a literature review of studies (n = 12) in experimental animals and human subjects (n = 12) and evaluated the evidence regarding the impact of administration of ACEIs and ARBs on ACE2 expression. We prioritized studies that assessed ACE2 protein expression data, measured directly or inferred from ACE2 activity assays. The findings in animals are inconsistent with respect to an increase in ACE2 expression in response to treatment with ACEIs or ARBs. Control/sham animals show little to no effect in the plurality of studies. Those studies that report increases in ACE2 expression tend to involve acute injury models and/or higher doses of ACEIs or ARBs than are typically administered to patients. Data from human studies overwhelmingly imply that administration of ACEIs/ARBs does not increase ACE2 expression. Available evidence, in particular, data from human studies, does not support the hypothesis that ACEI/ARB use increases ACE2 expression and the risk of complications from COVID-19. We conclude that patients being treated with ACEIs and ARBs should continue their use for approved indications.